Assisted extraction of rosemary antioxidants with green solvents - Rodríguez Rojo, Soraya (2012)
The use of natural antioxidants in the food industry has increased in the last years and there is a growing interest in improving the extraction processes using GRAS (general recognize as safe) solvents. In this work the extraction of antioxidants from rosemary with ethanol and water as solvents has been studied using different extraction processes (conventional, microwave assisted – MAE – and ultrasound assisted – USAE –) and plant pretreatments (deoiled and milled, deoiled and fresh plant). Total phenolic compounds in the extracts were determined by the Folin–Ciocalteu assay and HPLC with UV detection was employed for the quantitation of the main antioxidant compounds: rosmarinic acid and carnosic acid. The antioxidant activity of the extract was determined by the DPPHradical dot scavenging assay. The double pretreatment, deoiling by solvent free microwave extraction (SFME) and milling, has shown to be essential to overcome inner mass transfer limitations. Extraction efficiency can be additionally enhanced by microwave and ultrasound assisted extraction process, being this latter more significant in aqueous extracts.